Factorial validation of the Malay version of multidimension scale of perceived social support among a group of psychiatric patients - Ng, Chong Guan; Mohamad Shariff, Nurashikin (Malaysian Journal of Psychiatry, 2012)
Introduction: There is increasing awareness of the contribution of perceived social support (PSS) to emotional and physical well-being. Numerous scales measuring PSS have been developed, including the widely used Multidimensional Scale of Perceived Social Support (MSPSS). The psychometric properties of the MSPSS have been demonstrated in diverse samples, however mostly are conducted in English. Malay is the official language in Malaysia, and this study was conducted to provide evidence of the validity and reliability of a Malay version MSPSS (MSPSS-M) suited for our population. Methods: This is a cross sectional study. The sociodemographic and clinical information of the selected patients from psychiatric outpatient clinic over a 3-month period, were obtained via predesigned questionnaire, interviews and medical records. Assessment of psychiatric symptoms and social support were measured by various instruments including the Brief Psychiatric Rating Scale (BPRS-E), Depressive, Anxiety and Stress Scale (DASS) and MSPSS-M. Results: Data were reported for 228 psychiatric outpatients with the mean age of 40.3 years old. The 3-factor structure of the MSPSS-M (significant others, family, and friends) fitted the data well. The MSPSS-M showed good internal consistency (Cronbach a of 0.89) and validity. The scores of the total subscales for MSPSS-M were negatively correlated with the depression subscale in DASS (p<0.05). BPRS was negatively correlated with significant others (P<0.01) compared to the other two subscales in MSPSS-M. Conclusions: The Malay version MSPSS (MSPSS-M) is a psychometrically valid instrument with high internal consistency, which is useful in assessing perceived social support in Malaysian population.